In vivo delivery of plasmid DNA by lipid nanoparticles: the influence of ionizable cationic lipids on organ-selective gene expression. (27th April 2022) - Algarni, Azizah; Pilkington, Emily H.; Suys, Estelle J. A.; Al-Wassiti, Hareth; Pouton, Colin W.; Truong, Nghia P.
Abstract : Not all ionizable lipids are the same – choosing the right one is critical to the success of lipid nanoparticles for different applications. Abstract : Ionizable cationic lipids play a critical role in developing new gene therapies for various biomedical applications, including COVID-19 vaccines. However, it remains unclear whether the formulation of lipid nanoparticles (LNPs) using DLin-MC3-DMA, an optimized ionizable lipid clinically used for small interfering RNA (siRNA) therapy, also facilitates high liver-selective transfection of other gene therapies such as plasmid DNA (pDNA). Here we report the first investigation into pDNA transfection efficiency in different mouse organs after intramuscular and intravenous administration of lipid nanoparticles (LNPs) where DLin-MC3-DMA, DLin-KC2-DMA or DODAP are used as the ionizable cationic lipid component of the LNP. We discovered that these three benchmark lipids previously developed for siRNA delivery followed an unexpected characteristic rank order in gene expression efficiency when utilized for pDNA. In particular, DLin-KC2-DMA facilitated higher in vivo pDNA transfection than DLin-MC3-DMA and DODAP, possibly due to its head group p K a and lipid tail structure. Interestingly, LNPs formulated with either DLin-KC2-DMA or DLin-MC3-DMA exhibited significantly higher in vivo protein production in the spleen than in the liver. This work sheds light on the importance of the choice of ionizable cationic lipid and nucleic acid cargo for organ-selective gene expression. The study also provides a new design principle towards the formulation of more effective LNPs for biomedical applications of pDNA, such as gene editing, vaccines and immunotherapies.